The expression of Cx43, TGFβ/Smads signaling pathway and PCNA in the occurence and development of gastric carcinoma and the relationship among them (Journal of Pathology of Nepal, 2015)
Background: To detect the Protein expression level of Cx43, Smad4 and PCNA in normal and gastric carcinoma tissue by immunohistochemistry, western blotting and RT-PCR method.Materials and Methods: Immunohistochemistry and western blotting were adopted to detect the expression and expression level of Cx43, Smad4 and PCNA protein in normal and carcinomatous gastric tissue. Experimental data were analyzed by combining clinical pathology data using statistical tools.Results: The expression levels of Cx43 and Smad4 in carcinomatous gastric tissue were lower than they were in normal gastric tissue. The expression level of PCNA in carcinomatous gastric tissue was higher than that in normal gastric tissue. The expression levels of Cx43, Smad4 and PCNA in groups of age and gender is not significant. The expression of Cx43, Smad4 and PCNA in different clinic pathologic features of carcinomatous gastric tissue which includes degrees of pathological differentiation, lymph node metastasis condition, depth of tumor invasion and TNM stages is statistically significant. With the progression of gastric carcinoma, the expression levels of Cx43 and Smad4 were decreased, conversely PCNA showed a high expression level.Conclusion:  The protein and mRNA expressions of Cx43, Smad4 and PCNA were significantly different between normal gastric tissue and gastric carcinoma and also were concerned with degree of differentiation, lymph node metastasis, TNM stages and depth of invasion, though not significant with age and gender. This suggests that they may play an important role in occurrence and development of gastric carcinoma, but also may have some interaction.Journal of Pathology of Nepal (2015) Vol. 5, 696-704